Subglacial roughness of the former Barents Sea ice sheet - Gudlaugsson, Eythor; Humbert, A.; Winsborrow, Monica; Andreassen, Karin (Journal of Geophysical Research: Earth Surface, 2013)
The roughness of a glacier bed has high importance for the estimation of the sliding velocity and can also provide valuable insights into the dynamics and history of ice sheets, depending on scale. Measurement of basal properties in present-day ice sheets is restricted to ground-penetrating radar and seismics, with surveys retrieving relatively coarse data sets. Deglaciated areas, like the Barents Sea, can be surveyed by shipborne 2-D and 3-D seismics and multibeam sonar and provide the possibility of studying the basal roughness of former ice sheets and ice streams with high resolution. Here, for the first time, we quantify the subglacial roughness of the former Barents Sea ice sheet by estimating the spectral roughness of the basal topography. We also make deductions about the past flow directions by investigating how the roughness varies along a 2-D line as the orientation of the line changes. Lastly, we investigate how the estimated basal roughness is affected by the resolution of the basal topography data set by comparing the spectral roughness along a cross section using various sampling intervals. We find that the roughness typically varies on a similar scale as for other previously marine-inundated areas in West Antarctica, with subglacial troughs having very low roughness, consistent with fast ice flow and high rates of basal erosion. The resolution of the data set seems to be of minor importance when comparing roughness indices calculated with a fixed profile length. A strong dependence on track orientation is shown for all wavelengths, with profiles having higher roughness across former flow directions than along them.